2010
DOI: 10.1124/dmd.110.035402
|View full text |Cite
|
Sign up to set email alerts
|

Organic Cation Transporter-Mediated Renal Secretion of Ipratropium and Tiotropium in Rats and Humans

Abstract: ABSTRACT:Ipratropium bromide (ipratropium) and tiotropium bromide (tiotropium), anticholinergic agents with bronchodilating properties, are used to treat patients with chronic obstructive pulmonary disease. Because they are actively secreted into urine, the interaction of these agents with organic cation transporters (OCTs/Octs) was examined in rat kidney slices and in cultured cells expressing rat Oct (rOct) or human OCT (hOCT). Uptake of radiolabeled ipratropium in rat kidney slices was significantly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 31 publications
2
18
1
Order By: Relevance
“…However, major anticholinergics, ipratropium bromide (IPR) and tiotropium bromide, which are chemically related to atropine,1 are highly hydrophilic and unlikely to cross the plasma membrane by diffusion. Early pharmacokinetic studies indicated that their renal clearances are several fold greater than the glomerular filtration rate,2,3 and we subsequently demonstrated that these anticholinergics are recognized and transported by human organic cation/carnitine transporters (OCTN1/ SLC22A4 and OCTN2/ SLC22A5 ),4 as well as human and rat organic cation transporters (OCT1/ SLC22A1 and OCT2/ SLC22A2 ), indicating that vectorial transport mediated by these organic cation transporters plays a key role in efficient renal secretion of these compounds 5…”
Section: Introductionsupporting
confidence: 51%
“…However, major anticholinergics, ipratropium bromide (IPR) and tiotropium bromide, which are chemically related to atropine,1 are highly hydrophilic and unlikely to cross the plasma membrane by diffusion. Early pharmacokinetic studies indicated that their renal clearances are several fold greater than the glomerular filtration rate,2,3 and we subsequently demonstrated that these anticholinergics are recognized and transported by human organic cation/carnitine transporters (OCTN1/ SLC22A4 and OCTN2/ SLC22A5 ),4 as well as human and rat organic cation transporters (OCT1/ SLC22A1 and OCT2/ SLC22A2 ), indicating that vectorial transport mediated by these organic cation transporters plays a key role in efficient renal secretion of these compounds 5…”
Section: Introductionsupporting
confidence: 51%
“…This clearly does not impede their usefulness as inhaled drugs. However, the fact that both are substrates of organic cation transporter proteins (OCTs) may facilitate their transport through the lungs since this family of drug transporters is expressed in the lung [32,33]. Further work is required in the future to fully understand if and how absorptive drug transporters in the lung can be exploited to enhance inhaled drug delivery.…”
Section: Absorptionmentioning
confidence: 99%
“…After washing and removal of unattached cells, leaving a semiconfluent cell monolayer (.90% confluent), uptakes were performed at 1 mM substrate concentration in KHL. The activities of uptake transporters were tested with several well characterized substrates: rosuvastatin (AstraZeneca), OATPs (Ho et al, 2006); fexofenadine, OATPs (Cvetkovic et al, 1999); ipratropium, OCTs (Nakanishi et al, 2011); and taurocholate, NTCP (Ozawa et al, 2004). Rosuvastatin is also an NTCP substrate in human but not rat cells (Ho et al, 2006).…”
Section: Methodsmentioning
confidence: 99%